The use of nano-enabled technologies to diagnose dengue virus infections - Basso, Caroline R. [UNESP]; Crulhas, Bruno P. [UNESP]; Castro, Gustavo R. [UNESP]; Pedrosa, Valber A. [UNESP] (Elsevier, 2021)
Neglected diseases are caused by infectious agents or parasites and they are endemic in low-income populations living worldwide. Among these diseases, one finds dengue fever, which affects poor populations living in tropical and subtropical developing countries that report thousands of deaths on a yearly basis. Dengue fever is transmitted to individuals through the bite of contaminated mosquitos, a fact that favors outbreaks at the national scale. Nowadays, dengue diagnosis tests are performed in laboratories, mainly based on serological tests. However, this methodology has limitations such as high cost and the long time necessary to get to the results. Therefore, it is necessary to develop a new reliable and low-cost methodology to enable quick disease diagnosis. Recently, biosensors have emerged in the technological field as analytical tools capable of identifying pathogens based on the use of gold nanoparticles. Therefore, the aim of the current study is to briefly describe restrictions observed in conventional methodologies and the development of new methodologies focused on the fast and effective diagnosis of dengue virus in real serotype samples, based on the use of modified nanostructures; these nanostructures bind to their respective antigens and allow immediate color change. The current article has summarized published studies about fast diagnostic tests used for the biomolecular diagnosis of dengue fever.
Keywords: Biosensors; Dengue; Diagnosis; Naked-eye detection; Nanostructures